HAEMOSTATIC EFFECT OF ETHANOLIC EXTRACT OF Ageratum conyzoides L TO STRAINS OF MICE MALE SWISS WEBSTER INDUCED WITH COMBINATION OF ASPIRIN, CLOPIDOGREL AND ENOXAPARIN - Sukmawan, Yedy Purwandi; Suhendy, Hendy (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Bleeding complications are a common concern with the use of combination of antiagregations and anticoagulant agents especially on acute coronary syndrome treatment. In selected situations such as life-threatening, reversing may be desired, but no specific antidotum for the newer agents such as enoxaparin, fondaparinux, levirudin, bivalirudin, and argatroban. Ageratum conyzoides L is a medicinal plants that have a hemostatic effect. The objective of the study is to know the hemostatic effect of A. conyzoides L to induction of acetosal, clopidogrel, and enoxaparin. Methods: A total of 20 mice are divided into five groups that are normal, negative, positive, Test I and II. There were no treatment for normal, induction of drugs combination for negative, induction of drugs combination and tranexamic acid for positive, induction of drugs combination and ethanolic extract of A. conyzoides L (100 mg/Kg BW) for Test I, induction of drugs combination and ethanolic extract of A. conyzoides L (250 mg/Kg BW) for Test II. Results: The Test Groups I and II showed reversing of clotting time to normal baseline and shown a significant difference (p<0.05) compared with the negative group. In addition, the Test Groups I and II showed significant difference (p<0.05) of bleeding time compared with the negative group and the Test II (250 mg/Kg BW) shown reversing of bleeding time to normal baseline. Conclusion: The hemostatic effect showed by ethanolic extract of A. conyzoides L to induction of combination acetosal, clopidogrel and enoxaparin are very valuable for reversing agent novel.